Performance of different photovoltaic-thermal (PVT) configurations integrated on prototype test cells: An experimental approach. (15th December 2017) - Tomar, Vivek; Tiwari, G.N.; Bhatti, T.S.
Highlights: Analytical model for PVT configurations integrated on test cells is presented. Dynamic behaviour of PVT configurations is monitored in outdoor condition. Test cells based experiments are performed for comparative analysis. Constant temperature mode is attained for test cell by varying air mass flow rate. Thermal characteristic equations are developed for PVT configurations. Abstract: Analytical model for temperature dependent electrical and thermal efficiency for four different photovoltaic-thermal configurations integrated on identical prototype test cells namely; Case 1: glass to glass photovoltaic with duct integrated on a test cell, Case 2: glass to glass photovoltaic without duct integrated on a test cell, Case 3: glass to tedlar photovoltaic with duct integrated on a test cell and, Case 4: glass to tedlar photovoltaic without duct integrated on a test cell is developed in absence of ambient air exchange and experimentally validated in New Delhi's winter and summer seasonal conditions. The glass to glass photovoltaic module gives better performance in both electrical as well as thermal aspects, and gives daily average ηm 11.91% and 11.96% in summer whereas in winter, it gives 12.65% and 12.70% for case 1 and 2 respectively. Similarly, daily average ηith was 32.77% and 25.44% for case 1 and 2 respectively in winter. Ducted cases 1 and 3 have higher ηm and ηith due to the large heat dissipation capacity. Constant temperature mode operations inside test cells were attained, and we also discuss the effect of varying mass flow rate on electrical efficiency for ducted cases. Further, the yearly-round electrical, thermal, overall thermal, and overall exergy efficiencies for case 1 were found respectively 10.41%, 34.35%, 61.52% and 13.72% under typical New Delhi weather condition. The characteristic equations for all four cases were also been developed.